IoT in education: integration of objects with virtual academic communities (2016)
Internet has changed the way people interact and education has not been immune to this change, which has created new forms of interaction between teachers and students that helps to improve the teaching and learning process, and expands the context in which students learn. Moreover, with the integration of objects to the Internet, new possibilities for applications and services in domains such as education are available, where its use can lead to innovations that could facilitate the teaching-learning process. In this paper a new model for integrating objects to Virtual Academic Communities (VAC) is proposed. Tests of the proposed model were performed by the implementation of a case study, and the outcomes show that using IoT provides a more engaging learning environment for students and more data about the learning process to help teachers to enhance their knowledge about the learning pace of their students and their learning difficulties